Impact of post-breeding administration of hCG and flunixin meglumine on luteal function and pregnancy rates in anestrous Nili-Ravi buffaloes - Ejaz Ahmad; Muhammad Muzammal Niaz; Muhammad Saleem Akhtar; Muhammad Rizwan Yousuf; Muhammad Zahid Tahir; Tanveer Ahmad (Revista Científica)
This study was conducted to determine the impact of post-breeding administration of human chorionic gonadotropin hormone (hCG) and flunixin meglumine on luteal function and pregnancy rates in postpartum anoestrous Nili-Ravi buffaloes synchronized through a CIDR-GnRH based protocol during low breeding season. It was hypothesized that administering flunixin meglumine, an inhibitor of PGF2α synthesis, alone or in combination with hCG before implantation will increase the pregnancy rate by improving luteal functions in buffaloes. The sixty buffaloes (having a postpartum period of 90-120 days) were synchronized through the CIDR-GnRH protocol. Briefly, CIDR was placed intravaginally in all buffaloes for 7 days, then an injection of PGF2α was given on day 06 and GnRH on day 09. Timed artificial insemination (TAI) was done at 14-16 hrs following GnRH. After TAI, animals were randomly divided into four groups for different treatments. The T1 (n=15) buffaloes were given IM injection of hCG (3000 IU/animal) on day 07 after TAI. The T2 (n=15) buffaloes received an IM injection of flunixin meglumine (1.1mg/kg; b.i.d.) on days 14-15 post-TAI. The T3 (n=15) buffaloes received IM injections of hCG (3000 IU/animal) on day 07 and IM injection of flunixin meglumine (1.1mg/kg; b.i.d.) on day 14-15 post-TAI. In the T4 group (n=15), the control group received IM injection of normal saline on day 7 and day 14-15 after TAI. The size of the corpus luteum was measured by scanning ovaries through trans- rectal ultrasonog-raphy, and blood samples for serum progesterone assessment were collected on day 14 and day 20 post-TAI. Progesterone level was measured through ELISA. The pregnancy was diagnosed through ultrasonography on day 35 post-TAI. The results showed that the mean progesterone concentration was higher (p<0.05) in pregnant T1 and T3 buffaloes on day 14 post-TAI. However, progesterone concentration was similar in all groups on day 20 post-TAI. The corpus luteum size was higher (p<0.05) in pregnant buffaloes of group T1 and T3 at days 14 and 20. The pregnancy rates were higher (p<0.05) in T1 and T3 compared to T2 and Control Group. It is concluded that post-breeding administration of hCG improved luteal functions and pregnancy rate. However, flunixin meglumine alone or combined with hCG did not impact these parameters in Nili-Ravi buffaloes during the low breeding season.